Best Paper Selection (Yearbook of Medical Informatics, 2018)
Humbert M, Ayday E, Hubaux JP, Telenti A. Quantifying Interdependent Risks in Genomic Privacy. ACM Transactions on Privacy and Security 2017;20(1):3 https://dl.acm.org/citation.cfm?id=3035538Yuan J, Malin B, Modave F, Guo Y, Hogan WR, Shenkman E, Bian J. Towards a privacy preserving cohort discovery framework for clinical research networks. J Biomed Inform 2017;66:42-51 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5316314/Ohno-Machado L, Sansone SA, Alter G, Fore I, Grethe J, Xu H, Gonzalez-Beltran A, Rocca-Serra P, Guraraj AE, Bell E, Soysal E, Zong N, Kim HE. Finding useful data across multiple biomedical data repositories using DataMed. Nat Genet 2017;49(6):816-9 https://www.nature.com/articles/ng.3864Wan Z, Vorobeychik Y, Xia W, Clayton EW, Kantarcioglu M, Malin B. Expanding access to large-scale genomic data while promoting privacy: a game theoretic approach. Am J Hum Genet 2017;100(2):316-22 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5294764/Gilbert M, Bonnell A, Farrell J, Haag D, Bondyra M, Unger D, Elliot E. Click yes to consent: incorporating informed consent into an internet-based testing program for sexually transmitted and blood-borne infections. Int J Med Inform 2017;105:38-48 https://www.sciencedirect.com/science/article/pii/S1386505617301697?via%3Dihub